A new living species of the genus Ctenomys (Rodentia: Ctenomyidae) from central-western Argentina - Raquel Alvarado-Larios; Pablo Teta; Pablo Cuello; J. Pablo Jayat; Andrea P. Tarquino-Carbonell; Guillermo D’Elía; Paula Cornejo; Agustina A. Ojeda (Vertebrate Zoology, 2024)
Abstract The genus Ctenomys Blainville, 1826 includes 68 living species of small to medium-sized (100–1200 g) caviomorph rodents of subterranean habits. During the last decade, this genus has been the subject of numerous taxonomic studies, including the description of new species and the proposal of novel synonyms. Based on phylogenetic analysis of mitochondrial DNA sequences and qualitative and quantitative morphological traits, here we review the species boundaries of the tuco-tucos of the species group of C. mendocinus and describe a new species. The new species is morphologically distinct from other phylogenetically and geographically close species of Ctenomys (e.g., C. fochi, C. mendocinus), showing several differences in their craniodental traits (e.g., proportionally longer nasals and less globose tympanic bullae). The new species occurs in montane grasslands and shrublands of northwestern Mendoza (ca. 2710 m a.s.l.) and in lowlands (ca. 1000 m a.s.l.) of the Monte Desert ecoregion in an area highly impacted by accelerated processes associated with the wine industry.